2020
DOI: 10.1101/2020.08.30.274597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ribosome inhibition byC9ORF72-ALS/FTD-associated poly-PR and poly-GR proteins revealed by cryo-EM

Abstract: Toxic dipeptide repeat (DPR) proteins are produced from expanded G4C2 hexanucleotide repeats in the C9ORF72 gene, which cause amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Two DPR proteins, poly-PR and poly-GR, repress cellular translation but the molecular mechanism remains unknown. Here we show that poly-PR and poly-GR of ≥ 20 repeats inhibit the ribosome’s peptidyl-transferase activity at nanomolar concentrations, comparable to specific translation inhibitors. High-resolution cryo-E… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Early studies in drosophila suggested that toxicity arises not from the expanded RNA transcripts but from dipeptides, and particularly those containing arginine 19 . Other reports have also pointed to directly neurotoxic effects of these peptides 23,[53][54][55][56][57][58][59] , although directly toxic effects of the expanded RNA transcript have also been recently described 60 . Our findings strongly encourage the view that suppressing the expression of the mutant alleles of C9ORF72 may be clinically beneficial, regardless of whether the primary benefit is mediated by reduction in mutant transcripts or polydipeptide levels.…”
Section: Aso5-2 Is Non-toxic In Large Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies in drosophila suggested that toxicity arises not from the expanded RNA transcripts but from dipeptides, and particularly those containing arginine 19 . Other reports have also pointed to directly neurotoxic effects of these peptides 23,[53][54][55][56][57][58][59] , although directly toxic effects of the expanded RNA transcript have also been recently described 60 . Our findings strongly encourage the view that suppressing the expression of the mutant alleles of C9ORF72 may be clinically beneficial, regardless of whether the primary benefit is mediated by reduction in mutant transcripts or polydipeptide levels.…”
Section: Aso5-2 Is Non-toxic In Large Animalsmentioning
confidence: 99%
“…Both sense and antisense transcripts encompassing the HRE in V1 and V3 generate RNA foci and undergo translation into atypical, aggregation-prone dipeptide repeat (DPR) proteins in all open reading frames [14][15][16][17] . These unusual DPRs are toxic in several experimental model systems [18][19][20][21][22][23] Despite important advances in elucidating the molecular pathology of the expanded hexanucleotide repeats, there are no meaningful therapies for C9ORF72-related ALS or FTD 24,25 .…”
Section: Introduction 422 Wordsmentioning
confidence: 99%
“…25% or less). Such lengths would be sufficient to fill the ribosome exit tunnel and stall through an electrostatic jamming mechanism as previously proposed (1719). However, the most effective stalling required longer dipeptide lengths (>30 repeats for poly-GR (60 amino acids) and >50 repeats for poly-PR (100 amino acids)) to stall more than 50%, and indeed did so in a length-dependent manner, suggesting that emergent DPR chain is involved in stalling.…”
Section: Discussionmentioning
confidence: 59%
“…However, the most effective stalling required longer dipeptide lengths (>30 repeats for poly-GR (60 amino acids) and >50 repeats for poly-PR (100 amino acids)) to stall more than 50%, and indeed did so in a length-dependent manner, suggesting that emergent DPR chain is involved in stalling. A preprint study suggested that the addition of short synthetic 20×PR and 20×GR polypeptides strongly inhibited global translation in vitro and occluded the exit tunnel of eukaryotic 80S ribosomes (19). Accordingly, it is reasonable to predict that during R-rich DPR translation emergent poly-GR or poly-PR nascent chains could bind and block the exit tunnels of trailing ribosomes on the mRNA leading to obstruction of translation in trans, and a collateral aggregation of translational machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation